Persistent Increases in Ca(2+) Influx through Cav1.2 Shortens Action Potential And Causes Ca(2+) Overload-induced Afterdepolarizations and Arrhythmias - Zhang, Xiaoying (Basic Res Cardiol, 2015)
Persistent elevation of Ca(2+) influx due to prolongation of the action potential (AP), chronic activation of the β-adrenergic system and molecular remodeling occurs in stressed and diseased hearts. Increases in Ca(2+) influx are usually linked to prolonged myocyte action potentials and arrhythmias. However, the contribution of chronic enhancement of Cav1.2 activity on cardiac electrical remodeling and arrhythmogenicity has not been completely defined and is the subject of this study. Chronically increased Cav1.2 activity was produced with a cardiac specific, inducible double transgenic (DTG) mouse system overexpressing the β2a subunit of Cav (Cavβ2a). DTG myocytes had increased L-type Ca(2+) current (I(Ca-L)), myocyte shortening, and Ca(2+) transients. DTG mice had enhanced cardiac performance, but they died suddenly and prematurely. Telemetric electrocardiograms revealed shortened QT intervals. The action potential duration (APD) were shortened in DTG myocytes due to significant increases of potassium currents and channel abundance. However, shortened AP in DTG myocytes did not fully limit excess Ca(2+) influx and increased the peak and tail I(Ca-L). Enhanced ICa promoted sarcoplasmic reticulum (SR) Ca(2+) overload, diastolic Ca(2+) sparks and waves, and increased NCX activity, causing increased occurrence of early and delayed afterdepolarizations (EADs and DADs) that may contribute to premature ventricular beats and ventricular tachycardia. AV blocks that could be related to fibrosis of the AV node were also observed. Our study suggests that increasing I(Ca-L) does not necessarily result in AP prolongation but causes SR Ca(2+) overload and fibrosis of AV node and myocardium to induce cellular arrhythmogenicity, arrhythmias and conduction abnormalities.